2022
DOI: 10.3389/fphy.2022.988275
|View full text |Cite
|
Sign up to set email alerts
|

Importance of exponentially falling variability in heat generation on chemically reactive von kármán nanofluid flows subjected to a radial magnetic field and controlled locally by zero mass flux and convective heating conditions: A differential quadrature analysis

Abstract: Owing to the various physical aspects of nanofluids as thermally enhanced working fluids and the significance of swirling flows in rheological devices as well as in the spin coating and lubrication applications, the current comprehensive examination aimed to explore the important features of spinning flows of chemically reactive Newtonian nanofluids over a uniformly revolving disk in the existence of a radially applied magnetic field along with an exponentially decaying space-dependent heat source, in the case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Because of the nonlinearity mathematical character of the governing subsystems false{SF,SnormalΘfalse}$\{ {{S}_F,{S}_\Theta } \}$ of Equation () and their whole differential coupling structures, the dimensionless quantities false{Ffalse(ξfalse),Θfalse(ξfalse),Cfr,Nurfalse}$\{ {F^{\prime}( \xi ),\Theta ( \xi ),{C}_{fr},N{u}_r} \}$ featuring the resulting coupled nonlinear boundary values problem can be generated numerically through GDQ's and NR's procedures [86–90] (i.e., by connecting computationally the generalized differential quadrature and Newton's‐Raphson procedures) based on Shu's algorithm [91] as clarified schematically in the flowchart of Figure 3. Moreover, the proposed GDQ's‐NT solution methodology is among the most important iterative collocation techniques due to its robustness and flexibility in solving such flow problems with an upper level of precision.…”
Section: Gdq's‐nr Solution Methodology With Multiple Authenticationsmentioning
confidence: 99%
“…Because of the nonlinearity mathematical character of the governing subsystems false{SF,SnormalΘfalse}$\{ {{S}_F,{S}_\Theta } \}$ of Equation () and their whole differential coupling structures, the dimensionless quantities false{Ffalse(ξfalse),Θfalse(ξfalse),Cfr,Nurfalse}$\{ {F^{\prime}( \xi ),\Theta ( \xi ),{C}_{fr},N{u}_r} \}$ featuring the resulting coupled nonlinear boundary values problem can be generated numerically through GDQ's and NR's procedures [86–90] (i.e., by connecting computationally the generalized differential quadrature and Newton's‐Raphson procedures) based on Shu's algorithm [91] as clarified schematically in the flowchart of Figure 3. Moreover, the proposed GDQ's‐NT solution methodology is among the most important iterative collocation techniques due to its robustness and flexibility in solving such flow problems with an upper level of precision.…”
Section: Gdq's‐nr Solution Methodology With Multiple Authenticationsmentioning
confidence: 99%
“…Rasool et al's [ 20 ] investigation of EMHD-driven nanofluid flow through convective Riga surface for submissive control of alumina nanoparticles in aquatic medium. Wakif et al's [ 21 ] analysis highlights the significance of heat generation variability that is exponentially decreasing on chemically reactive nanofluid flows that are exposed to a radial magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…Wakif and Shah [8] found that the convective heating reinforced the occurrence of the thermophoresis process. Besides, Wakif et al [9] found that the thermomigration of nanoparticles can be reinforced more via the intensification in the convective process, the thermomigration of nanoparticles, and the activation energy. The effects of thermal radiation and surface roughness on the complex dynamics of water conveying alumina and copper oxide nanoparticles were considered in Wakif et al [10].…”
Section: Introductionmentioning
confidence: 99%